Safeguarding National Interests in AfricaA Study of Economic Threats and Their Implications for the Sovereignty of African States - (:unkn) unknown (My University, 2021)
This book analyzes the national interests of African countries. Unemployment, rebellion, civil wars, terrorism and their economic implications, along with capital flight, represent serious threats to the stability and sovereignty of African states.Additionally, poorly negotiated trade agreements and treaties, the erosion of cultural identity, and systemic corruption contribute, on the one hand, to the fragility of African countries’ trade balances and, on the other hand, to the destabilization of their institutional structures.In short, national interest must be a central concern for African states—economically, politically, and culturally. But how can this be achieved from a strictly economic standpoint?This book seeks to answer that question.
Keywords: African Research